2009
DOI: 10.1007/s00221-009-1930-2
|View full text |Cite
|
Sign up to set email alerts
|

Primate disconjugate eye movements during the horizontal AVOR in darkness and a plausible mechanism

Abstract: Disconjugate eye movements during the horizontal angular vestibulo-ocular reflex (AVOR) evoked in response to steps or pulses of head velocity have been previously reported in lateral eyed animals. In this study, we measured binocular responses to sustained sinusoidal and pseudo-random vestibular stimuli in yaw, delivered in darkness, in both human and monkey. The vestibular stimuli used in our experiments had peak velocities in the range of 120-200 degrees /s, frequencies in the range of 0.17-0.5 Hz, and dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 50 publications
1
5
2
Order By: Relevance
“…head position is small and negative for positive head velocities and positive for negative head velocities (small slope). This is consistent with the observations reported by [35] for control subjects. However, in the case of left canal plugging (light gray trend), the magnitude of vergence has increased and it's gain re.…”
Section: Disconjugate Eye Movements In Darkness -Vergencesupporting
confidence: 83%
See 1 more Smart Citation
“…head position is small and negative for positive head velocities and positive for negative head velocities (small slope). This is consistent with the observations reported by [35] for control subjects. However, in the case of left canal plugging (light gray trend), the magnitude of vergence has increased and it's gain re.…”
Section: Disconjugate Eye Movements In Darkness -Vergencesupporting
confidence: 83%
“…However, binocular recordings of AVOR, delivered in darkness, in both human and monkey [35], show a considerable vergence component that is modulated with head velocity. Khojasteh and Galiana [35] suggested that a possible source for vergence responses in the dark could be a secondary effect of nonlinearities that are needed for modulation with sensori-motor context.…”
Section: Disconjugate Eye Movements In Darkness -Vergencementioning
confidence: 99%
“…Moreover, compared to the pure slow phase model, the peak-to-peak amplitude of the vergence component is smaller in the hybrid model since nystagmus serves to limit non-linear functions to smaller excursions on non-linear surfaces at the premotor level. Contrary to common belief, the AVOR is not purely con- jugate in the dark; binocular recordings during sinusoidal rotations in darkness clearly show a vergence component in the AVOR [12]. Fig.3.C presents both the recorded and simulated vergence component.…”
Section: Resultscontrasting
confidence: 55%
“…We have also compared our model performance in response to a specific rotation profile ( 180 deg/s at 1/6 Hz) where binocular records are available [12]. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In the earlier study, binocular eye position signals were measured by the EOG. Without a rigorous treatment of the EOG signals, it would be difficult to overcome its limitations (nonlinearity and baseline drifts) in order to provide an accurate assessment of the VOR conjugacy (Schlag et al 1983; Khojasteh and Galiana 2009). In the present study, binocular eye position signals were measured using a search coil technique that has high spatial/temporal resolution, and excellent linearity and stability (Robinson 1963).…”
Section: Discussionmentioning
confidence: 99%